Thymectomy in Juvenile Myasthenia Gravis Is Safe Regarding Long Term Immunological Effects - Popperud, Trine H.; Gul, Kiran A.; Brunborg, Cathrine; Olaussen, Richard W.; Abrahamsen, Tore G.; Osnes, Liv T.; Kerty, Emila (Frontiers in Neurology, 2021)
Thymectomy is an established treatment in adult MG and also recommended for the treatment of post-pubertal onset juvenile MG. Whether the youngest children should be thymectomized is still debated. Signs of premature aging of the immune system have been shown in studies on early perioperative thymectomy in children with congenital heart defect. In this retrospective cohort study the objective was to investigate the long-term effects of treatment related thymectomy on T cell subsets and T cell receptor rearrangement excision circles (TRECs) in peripheral blood of juvenile myasthenia gravis (MG) patients, as well as clinical occurrence of autoimmune disorders, malignancies and infectious diseases. Forty-seven patients with onset of myasthenia gravis before the age of 19 years were included; 32 (68.1%) had been thymectomized and 15 (31.8%) had not. They were studied at varying times after thymectomy (7–26 years). We found a significant lower number of naïve helper T cells (CD4+CD45RA+) with an increased proportion of memory helper T cells (CD4+CD45RO+), and a significant lower number of naïve cytotoxic T cells (CD8+CD27+CD28+) in the thymectomized patients. In addition they showed a significant reduction in the number of TRECs and proportion of recent thymic emigrants (RTE) compared to non-thymectomized patients. In none of them an increased frequency of malignancies or infections was found. Our findings indicate a premature aging of the immune system after thymectomy in juvenile MG, but associated clinical consequences could not be verified.